Desenvolvimento de um instrumento para identificação e análise da influência dos fatores contextuais no período gestacional - Silva, Clara Maria de Araujo (2024)
During the gestational period, numerous physiological adaptations occur to facilitate the maternal body's adjustment to fetal growth. It is crucial to consider the context in which pregnant women are situated, identifying potential social inequalities. However, in the literature, tools assessing contextual factors personal, economic, social, and cultural aspects of Brazilian pregnant women are scarce. Objective: Develop an instrument based on the International Classification of Functioning to identify and assess the influence of contextual factors during the gestational period in Brazilian women. Methods: A methodological study was conducted for instrument development using the Delphi Method and COSMIN guidelines. Ethical approval was obtained (CAEE: 63878222.1.0000.5504). The study comprised the following stages: 1- Definition of the construct, 2- Item selection and formulation; 3- Pre-test, with data collection from March to July 2023. Descriptive analysis characterized study participants. Data from the instrument construction process underwent specific analyses for each stage. Descriptive analyses identified relevant contextual factors and pre-test results. Bardin's discourse analysis was employed for qualitative data, and the instrument's content validity index assessed the instrument. Results: The study involved 22 experts in stage 2, evenly divided between subject experts and the target audience. In stage 3, 21 pregnant women participated, diverse in geographic location, mostly married or in stable unions, with high educational levels. Instrument development results showed variation in expert agreement on contextual factors' relevance, with the support network (90.9%), physical activity (72.7%), age, and prenatal care (63.6%) being the most relevant. Factors like profession, number of previous pregnancies, housing arrangement, and space for the newborn were considered relevant by 54.6% of experts. Factors such as mobility, race/ethnicity, education, housing conditions, and family income had agreement percentages below 50%. Regarding feasibility, the instrument was deemed easy, quick, and easily understandable for completion. Conclusion: Divergence exists between healthcare professionals and pregnant women regarding relevant contextual factors. Nevertheless, the developed instrument was considered suitable, relevant, and comprehensible, potentially serving as a valuable tool for research and clinical practice. The instrument comprises three assessment sections: the first being the cover page, the second covering personal factors, and the third addressing environmental factors. The cover page and personal factors sections enable the identification of individual respondent characteristics potentially correlating with measures found in the environmental factors section concerning the type of influence (positive or negative) of these factors. For measurement purposes, only responses from the environmental factors section are utilized.